2010
DOI: 10.1523/jneurosci.1062-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Frontostriatal Involvement in Task Switching Depends on Genetic Differences in D2 Receptor Density

Abstract: Recent studies suggest an association of dopamine D2 receptor (DRD2) availability with flexibility in reward-based learning. We extend these results by demonstrating an association of genetically based differences in DRD2 density with the ability to intentionally switch between nonrewarded tasks: noncarriers of the A1 allele of the DRD2/ANKK1-TaqIa polymorphism, associated with higher DRD2 density, show increased task-switching costs, increased prefrontal switching activity in the inferior frontal junction are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
140
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(158 citation statements)
references
References 74 publications
16
140
1
1
Order By: Relevance
“…Accordingly, the shallower the energy landscape of the respective neural network, the weaker the signal that IFJ and related regions have to produce in order to effect an updating of the task rule representation. This specific role of the IFJ during rule-based cognitive flexibility is supported by our earlier finding that IFJ activation during task switching, as well as the functional coupling between IFJ and the dorsal striatum, are modulated by the DRD2/ ANKK1-TaqIa polymorphism, that is, by a genetic variation that influences the density of DRD2 receptors in the striatum (Stelzel et al, 2010), which is related to the D1 receptor activation in pFC (Kellendonk et al, 2006;Laakso et al, 2005). Specifically, we demonstrated that persons with lower D2 receptor densities in the striatum, a state that is associated with increased dopamine activity (Laakso et al, 2005) and decreased D1 receptor activation in PFC, are more efficient in task switching and show less activity in the left IFJ (Stelzel et al, 2010)-the exact region whose activation and functional connectivity patterns were modulated by the spontaneous switching rate in the current study.…”
Section: The Individual Spontaneous Switching Rate Modulates Flexibilsupporting
confidence: 59%
See 1 more Smart Citation
“…Accordingly, the shallower the energy landscape of the respective neural network, the weaker the signal that IFJ and related regions have to produce in order to effect an updating of the task rule representation. This specific role of the IFJ during rule-based cognitive flexibility is supported by our earlier finding that IFJ activation during task switching, as well as the functional coupling between IFJ and the dorsal striatum, are modulated by the DRD2/ ANKK1-TaqIa polymorphism, that is, by a genetic variation that influences the density of DRD2 receptors in the striatum (Stelzel et al, 2010), which is related to the D1 receptor activation in pFC (Kellendonk et al, 2006;Laakso et al, 2005). Specifically, we demonstrated that persons with lower D2 receptor densities in the striatum, a state that is associated with increased dopamine activity (Laakso et al, 2005) and decreased D1 receptor activation in PFC, are more efficient in task switching and show less activity in the left IFJ (Stelzel et al, 2010)-the exact region whose activation and functional connectivity patterns were modulated by the spontaneous switching rate in the current study.…”
Section: The Individual Spontaneous Switching Rate Modulates Flexibilsupporting
confidence: 59%
“…The PPI approach aims at finding brain regions that are differentially coupled with the seed region, depending on specific psychological conditions. The IFJ area was chosen as seed for the PPI analyses as (i) it was shown to be critical for the updating of task representations ; (ii) its activation during task switching is modulated by genetically determined D2 receptor density (Stelzel et al, 2010), which directly relates it to the computational model that motivates the present work; (iii) it was activated for both task switching and distractor inhibition in the present study; and (iv) its activation was modulated by the individual spontaneous switching rate (cf. Results).…”
Section: Functional Connectivity Analysismentioning
confidence: 99%
“…Currently, the most effective treatments for SCZ principally antagonize this receptor (30). DRD2 density has been shown to be increased in the brains of schizophrenic patients (31). The rs1800497 locus, which was previously thought to be located in DRD2, has been identified within exon 8 of ANKK1 and likely modulates the function and expression of DRD2 due to its close proximity (32).…”
Section: Discussionmentioning
confidence: 99%
“…Note that, although no suprathreshold activity was present during task switching in this exact anterior prefrontal region identified in the PPI analysis, a post hoc analysis of the activation data with a lower threshold of p < .005, uncorrected for cluster size, revealed a small cluster related to task switching in the left anterior PFC (x = −48, y = 44; z = 8; k = 13; t max = 2.73) adjacent to the region found to be activated when the contrast for abstract rule switching was pooled across response hand repetitions and switches (Stelzel, Basten, Montag, Reuter, & Fiebach, 2010). Endogenous task preparation has previously been associated with activity in anterior lateral prefrontal regions (Forstmann, Brass, Koch, & von Cramon, 2005;Rowe et al, 2005) and might underlie the present pattern of connectivity.…”
Section: Abstract Rule Switchingmentioning
confidence: 97%
“…Are rules and intentions represented and maintained in this most anterior region of the cortex or are signals from there sent to more posterior regions to bias processing in regions that actually represent the task-relevant information? Although the role of the IFJ is usually seen as related to a specific process, namely the updating of task representations (Stelzel et al, 2010;Brass et al, 2005;Brass & von Cramon, 2002), some recent evidence from multivoxel pattern analysis suggests that activity in anterior PFC can be associated with the representation of abstract rules (Bode & Haynes, 2009;Haynes et al, 2007). Whether anterior prefrontal activity can be consistently decoded as being related to the representation of specific task rules-that is, whether abstract rules and goals are actually stored in the anterior PFC-is still under debate (Sakai, 2008).…”
Section: Abstract Rule Switchingmentioning
confidence: 99%